If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3x + -9 + 1 = 5x + 7x + -3 Reorder the terms: -9 + 1 + 6x + -3x = 5x + 7x + -3 Combine like terms: -9 + 1 = -8 -8 + 6x + -3x = 5x + 7x + -3 Combine like terms: 6x + -3x = 3x -8 + 3x = 5x + 7x + -3 Reorder the terms: -8 + 3x = -3 + 5x + 7x Combine like terms: 5x + 7x = 12x -8 + 3x = -3 + 12x Solving -8 + 3x = -3 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -8 + 3x + -12x = -3 + 12x + -12x Combine like terms: 3x + -12x = -9x -8 + -9x = -3 + 12x + -12x Combine like terms: 12x + -12x = 0 -8 + -9x = -3 + 0 -8 + -9x = -3 Add '8' to each side of the equation. -8 + 8 + -9x = -3 + 8 Combine like terms: -8 + 8 = 0 0 + -9x = -3 + 8 -9x = -3 + 8 Combine like terms: -3 + 8 = 5 -9x = 5 Divide each side by '-9'. x = -0.5555555556 Simplifying x = -0.5555555556
| 2+8v=-94 | | x^3+x^2-21x-45=0 | | 0.16x+27=28 | | 3(x+7)=6(x-1)-4 | | P=b+3a+2c | | 7y-3=6y+9 | | x/3-24=81 | | 5-2[5-(6y-2)]= | | -129-[7-8y-5(6y-2)]= | | 5y+7=42 | | 3(5x-7)=15 | | 4(3x+1)=20 | | -6-28=24+2x | | 4x-1=5x-3 | | 4(3x+1)=21 | | .2y+15=0 | | 6x-28=24+2x | | 6(3+9x)=8(x-2) | | -5x+8=33 | | -8x-57=73-3x | | 11x+16=3x+192 | | -4x+3.2=0.3 | | -2(4s-4)-8=-3(7s+3)-5 | | x^3+5x^2+3x-9=0 | | 11x-17=22 | | (0.8x-1)(8x-10)=0 | | 244-4x=41x+24 | | 7(x-3)-5(x^2-1)=x^2-5(x+2) | | 5x-15=3x+25 | | 2y^2+14y=-19 | | -10+7x=-73 | | 3x^2-27x=42 |